African Dacus (Diptera: Tephritidae); New Species and Data, with Particular Reference to the Tel Aviv University Collection - White, Ian M.; Goodger, Kim F. M. (Zootaxa, 2009)
Seventeen new species are described: Dacus abruptus, D. acutus, D. albiseta, D. brunnalis, D. insolitus, D. kaplanae, D. kurrensis, D. luteovittatus, D. magnificus, D. pseudapostata, D. pseudomirificus, D. senegalensis, D. transversalis, D. velutifrons, D. vestigivittatus, D. xanthinus, D. yaromi. Two species have changed status: D. devure Hancock is newly placed as a synonym of D. africanus Adams; D. mochii Bezzi stat.rev. is removed from synonymy with D. annulatus Becker and redescribed. Two subgeneric changes are made: D. nairobensis White and D. seguyi (Munro) are placed in sg. Lophodacus [both from sg. Didacus]. New descriptive data are presented for several species; these include first known male of D. gabonensis White, D. parvimaculatus White, D. seguyi and D. semisphaereus Becker; first known female of D. blepharogaster Bezzi, D. merzi White and D. nairobensis White. Revised host data are presented for Bactrocera mesomelas (Bezzi), and new male lure data for D. congoensis White, D. fuscovittatus Graham and D. pleuralis Collart. New country records are listed for a further sixteen species.